DEFISIT PRAGMATIK TUTURAN PENDERITA SKIZOFRENIA DI RS JIWA MENUR SURABAYA: KAJIAN PRAGMATIK KLINIS - Suryani, Yunita (Universitas Negeri Surabaya, 2015)
Pragmatic deficits are language imperfections caused by many factors. One of the factors causing a person to experience language imperfection is a medical factor. This study focused on (1) schizophrenic speech deficits, (2) deficits of external deixis (ecofora) schizophrenic speech, (3) deficit of schizophrenic conversation structure, (4) deficits of schizophrenic speech relevance, and (5) therapeutic against the pragmatic deficit of schizophrenic speech. This research is formulated and illustrated based on the actual phrase of speech found in linguistic facts as found in actual language usage, so that the research of this language is descriptive qualitative. The subject of this study is schizophrenic case study of patients in RSU Meniran Surabaya named Yt. The data in this research is a speech obtained through recording, transcription, reduction, classification and interpretation so as to produce a description of the focus that has been proposed. In the results of this study indicated that (1) Yt experience imperfections in acts of speech representative, directive, expressive, commissive, and declarative; (2) Yt experiencing imperfections in referring to a matter related to space, persona, and time; (3) Yt experiencing imperfections in understanding the structure of the conversation in the form of turning, overlap, and adjacency pairs; (4) Yt experiencing imperfections of revealing speech; (5) therapeutic helps restore the thought disorder suffered by Yt.